Rationale for prescription, and effectiveness of, upper limb orthotic intervention for children with cerebral palsy: a systematic review - Garbellini, S.; Robert, Y.; Randall, M.; Elliott, Catherine; Imms, C. (Informa Healthcare, 2018)
Purpose: To explore (i) reasons for upper limb orthosis prescription for children with cerebral palsy (CP), (ii) the link between reason and effect according to intended outcome and outcome measure utilized and (iii) to classify the prescribed orthoses using standard terminology. Method: A prospectively registered (center for reviews and dissemination: 42015022067) systematic review searched for experimental and observational studies investigating rigid/thermoplastic upper limb orthotic intervention for children aged 0–18 with CP. The Cochrane central register, MEDLINE, CINAHL, Embase, SCOPUS and Web of Science databases were searched. Included studies were assessed for risk of bias. Results: Sixteen studies met selection criteria. Two studies described a specific reason for orthosis prescription, six prescribed orthoses to manage a clinical symptom and eight did not describe a reason. Eight studies were analyzed for effect according to intended outcome with no clear connection found between reasons for prescription, outcome measures utilized and effect reported. Interpretation: The lack of evidence for upper limb orthotic intervention for children with CP leads to uncertainty when considering this treatment modality. Future research is needed to evaluate the effect of orthosis wear in relation to intended outcome utilizing robust methods and valid and reliable outcome measures. Implications for rehabilitation: Insufficient evidence exists about the reason for prescription of upper limb orthoses. The connection between reason for orthosis prescription, intended outcome, outcome measure utilized and observed effect is unclear. Recommend orthosis prescription to be accompanied by clear documentation of the aim of the orthosis and description using orthosis classification system terminology. Outcome measures consistent with the reason for orthosis prescription and intended outcome of the intervention are essential to measure effectiveness of the intervention.